(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Tell Helawa is a prehistoric and protohistoric settlement of Northern Mesopotamia located in the Erbil Plain, 28 km south-west of the modern city of Erbil, Kurdistan Region of Iraq. The site is investigated by the Italian Expedition in the Erbil Plain (MAIPE) of the University of Milan, directed by prof. L. Peyronel. The site of Helawa is occupied from the Neolithic to the Late Chalcolithic 3 (VII-IV millennium BC); the site seems then abandoned in the course of the Late Chalcolithic 3 and later reoccupied during the Late Bronze Age (II millennium BC). During the 2018 campaign, 37 clay bullets were found in Ubaid levels, investigated in the long step trench opened along the southern slope of the main mound. Widely distributed in different contexts across the ancient Near East and beyond, it is still unclear how they were produced and used. In this article, we analyze evidence of clay bullets from different ancient Near Eastern contexts, taking into account morphological, functional and contextual data with the aim of proposing techno-functional interpretations through the examination of the clay bullets found at Helawa.